SIMULASI DAN ANALISIS DAMPAK PLTS DAN BESS TERHADAP KESTABILAN FREKUENSI SISTEM KELISTRIKAN NUSA PENIDA - Harahap, RS; Kumara, INS; Sukerayasa, IW; Giriantari, IAD; Setiawan, IN; Ariastina, WG (Jurnal SPEKTRUM, 2024)
The islands of Nusa Penida, Nusa Lembongan, and Nusa Ceningan are some of the famous tourist destinations in Bali. The growth of tourism in the area has increased the demand for electrical energy. PLN is committed to improving infrastructure by building a solar power plant and BESS in Nusa Penida. This research aims to analyze the impact of implementing PLTS and Battery Energy Storage Systems (BESS) on the frequency of the electricity system in Nusa Penida. This research uses a simulation with two scenarios in three different conditions. Scenario 1 is simulated by releasing the Cogindo generating unit from the Nusa Penida electricity system with three conditions, namely an electricity system without PLTS and BESS, an electricity system with PLTS, and an electricity system with PLTS and BESS. Scenario 2 is simulated by removing the Ceningan feeder from the Nusa Penida electricity system with the same three conditions. Simulations were carried out to determine the effect of PLTS and BESS on frequency changes. The simulation results show that frequency changes are still within the limits regulated by the Minister of Energy and Mineral Resources Regulation Number 20 of 2020.